Mammal Hunting in the Special Use Zone and Buffer Tingo Maria National Park, Huánuco, Peru - Gonzales Guillén, Fiorella Nasha (2014)
Between the months of August to November 2011 were conducted 42 semi-structured interviews to assess the hunting of mammals in areas of special purpose (ZUE) and buffer (ZA) National Park Tingo María surveys. The results indicate that 43% of the population practiced hunting as a secondary activity, the main smallholder agriculture. The methodology used for hunting are the "tramperas" while the hunting is often 2-3 times a month. Hunting is more common after the wet season, it is selective and responds to the taste of meat that an economic need. Among the most hunted mammals include agouti Dasyprocta sp. and picuro Cuniculus paca, while animals higher biomass as the peccary Pecari tajacu are rare in the area, so it is recommended to increase the control of hunting of vulnerable species in the villages which are inside and in the vicinity of the Park.